Raised Uric Acid Level and Fetal Outcome in Hypertensive Disorders of Pregnancy - Singh, A; Sharma, P; Malla, R; Singh, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to find the relation of raised uric acid with fetal outcome in hypertensive disorders of pregnancy and to compare the fetal outcome with normal and raised uric acid level . Methods: This was a hospital based cross-sectional prospective comparative study done in Paropakar maternity and Women’s hospital conducted over three month period. Results: During the study period, a total of 126 cases of hypertensive disorders of pregnancy were identified among 3819 obstetric cases. The incidence of hypertensive disorders of pregnancy in this study was 3.3%. Fifty seven of them were found to have serum uric acid level <5.5 mg% (Group A), 43 of them were found to have serum uric acid level ≥5.5mg% (Group B). In those developing hyperuricemia 54.81% had mild hypertension, 40.91% had severe hypertension. Adverse perinatal outcome with serum uric acid level ≥5.5mg/dl had stillbirth in 7%, had low birth weight in 27.9%, 11.6 % were admitted in special care baby unit and 18.6 % had apgar <7 at five minute. Conclusions: Perinatal morbidity and mortality was increased in women with raised uric acid level except admission to special baby care unit Hypertensive disorders of pregnancy are associated with high maternal and perinatal morbidity and mortality. DOI: http://dx.doi.org/10.3126/njog.v9i1.11196 NJOG 2014 Jan-Jun; 2(1):78-81